Carbon dioxide utilisation in anaerobic digesters as an on-site carbon revalorisation strategy - Bajón Fernández, Yadira (Cranfield University, 2014)
The increasing carbon footprint of the water and organic waste sectors has led to water utilities to voluntarily include carbon mitigation approaches within their strategic plans and to an increase in research aimed at mitigating carbon dioxide (CO2) emissions. Injection of CO2 in anaerobic digesters (ADs) for its bioconversion into methane (CH4) has been identified as a potential solution. However, previous literature provided limited knowledge of the carbon benefits obtainable and presented conflicting information regarding the mechanisms of CO2 utilisation. This thesis investigated the potential of injecting exogenous CO2 into ADs for its bioconversion into CH4 to reduce CO2 emissions from water and organic waste facilities. Batch laboratory scale and continuous pilot-scale ADs enriched with CO2 were operated. A substrate dependant response to exogenous CO2 was reported for the first time and potential CO2 savings of up to 34% and 11% were estimated for sewage sludge and food waste batch ADs, respectively, injected with CO2 before the digestion process. Higher benefits in CH4 production were observed in sewage sludge ADs than in food waste units. An up to 2.4 fold increase in CH4 production during the 24 hours following saturation with CO2 was obtained in sewage sludge units, while benefit was limited to 1.16 fold in food waste ADs. Microbial community analyses were performed to elucidate CO2 fate mechanisms. An increase of up to 80% in the activity of Methanosaetaceae (obligate acetoclastic methanogen) was observed in sewage sludge ADs periodically enriched with CO2. Methanosaetaceae was scarce (4.3±1.7%) in food waste units, which was attributed to an inhibitory concentration of ammonia (4 gL-1 NH4-N). Based on Archaea analyses and on monitoring hydrogen (H2) and volatile fatty acids (VFA) speciation dynamics in a pilot-scale AD, it was proposed that exogenous CO2 is reduced by homoacetogenesis (Wood-Ljungdahl mechanism) and the acetate generated by this route is converted to CH4 by acetoclastic methanogenesis. Gas to liquid mass transfer was identified as limiting of the amount of dissolved CO2 loaded to an AD and the complex rheology of anaerobically digested media as detrimental for transfer performance. An increase of apparent viscosity (μa) from 130 to 340 cPo (typical variability of sewage sludge) reduced gas transfer efficiency (GTE) by 6 percentage points. The use of bubble columns was identified as suitable for further scaled-up units. Injection of CO2 could be performed in the digestate recirculation loop of single phase ADs or in the first phase of two phase ADs (TPADs), with CO2 sourced from off-gas of biogas upgrading technologies. It has been demonstrated that bioconversion of CO2 in ADs can reduce carbon footprint and increase CH4 production, with the possibility of becoming an on-site carbon revalorisation strategy.